Energy-efficient building renovation: Price-adjusted investments declining; trend reversal needed to reach climate targets - Martin Gornig; Katrin Klarhöfer (DIW Weekly Report, 2024)
In light of rising oil and gas prices, investments in energy-efficient building renovation in Germany have risen recently in nominal terms. In 2023, around 72 billion euros were spent on the energy-efficient renovation of residential, public, and commercial buildings, about 12 billion more than in 2021. Nevertheless, investments declined by over six percent in price-adjusted terms, as construction prices rose sharply during this time as well. To reach climate targets, however, significantly more real investments in energy-efficient building renovation are needed, as are framework conditions in Germany and Europe. Investment aid for energy-efficient renovation measures also plays an important role. The German Federal Government increased funding for these measures for 2024 to 16.7 billion euros. However, policymakers will need to provide even more funding in the future due to rising financing and construction costs if they actually want to increase the rate of energy-efficient building renovation.
Keywords: E22; Q40; 330; Energy-efficient building renovation; construction industry; building investment